Rekonstruksi Metode Menghafal dalam Pembelajaran Mufradat Bahasa Arab Berbasis Teori Multiple Intelligence di Pondok Pesantren - Al-Ghozali, M. Dzikrul Hakim; Mujizah, Silvia Nur (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
A Learning methods are an important component of the learning process. The method is a teacher's strategy to help students understand the material. This research aims to determine the memorization method in mufradat learning based on Multiple Intelligence theory in Islamic boarding schools, especially at the Darussalam Jombang Islamic Boarding School. This research uses a qualitative approach method. Data collection techniques were carried out using observation and interviews. Then, conclusions will be drawn from the data that has been obtained using the triangulation method. Based on the research that has been carried out, the results show that the memorization method applied at the Darussalam Islamic Boarding School is not to the intelligence characteristics of the students, so it has an effect on the student's learning outcomes. The memorization method that has been applied so far only focuses on one learning method without paying attention to class conditions and also the intelligence characteristics of the students, which then makes the learning process run less effectively and also produces less than optimal results because the students have difficulty receiving and understanding the learning material. A variety of media and other methods are needed that suit the intelligence characteristics of students so that they can easily receive and understand the material for maximum learning outcomes.